Makna Syukur dalam Upacara Adat Wu’u Nura di Desa Daniwato Solor Barat dan Perayaan Ekaristi: Tinjauan Perbandingan - Jawan, Fransiska Masandai; Intansakti Pius X; Tarihoran, Emmeria (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines in depth the meaning of gratitude expressed in the traditional Wu’u Nura ceremony in Daniwato Village, West Solor, as well as in the Eucharistic celebration, which stands as the central liturgy of the Catholic Church. The Wu’u Nura ceremony is a communal tradition of thanksgiving for the harvest, expressed through symbolic rituals, offerings of agricultural produce, collective prayers, and ceremonial practices that reflect a harmonious relationship between humans, nature, ancestors, and God. Through these rituals, the community strengthens social cohesion, cultural identity, and religious awareness that have been passed down across generations. In contrast, gratitude within the Eucharistic celebration is understood as an expression of faith and a theological response to God’s salvific grace manifested through Christ’s sacrifice, made present in the consecration of bread and wine. Using a qualitative method and comparative approach, this study reveals that although differing in expression, structure, and theological foundations, both practices uphold gratitude as a universal value that fosters spiritual relationships and social solidarity. The findings affirm that dialogue between local culture and Church liturgy—within the spirit of inculturation—can enrich the understanding of faith, deepen spiritual life, and support the preservation of meaningful local traditions. This study contributes significantly to cultural and theological scholarship, as well as pastoral efforts aimed at fostering harmony between religion and culture in pluralistic societies.